Equity-regarding poverty measures: Differences in needs and the role of equivalence scales - Udo Ebert (Luxembourg Income Study (LIS), 2008)
The paper investigates the definition of equity-regarding poverty measures when there are different household types in the population. It derives the implications of a between-type regressive transfer principle for poverty measures, for the choice of poverty lines and for the measurement of living standard. The role of equivalence scales which are popular in empirical work on poverty measurement is clarified.
Keywords: D63; I31; I32; 330; poverty measures; differences in needs; principle of transfers; equivalence scales; Armut; Messung; Privater Haushalt; Lebensstandard; Sozialer Indikator; Deutschland